1998
DOI: 10.1103/physrevb.58.15231
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of the in-plane penetration depth and fishtail inBi2Sr2Ca

Abstract: We report on the London penetration depth ab (0), measurements, and second peak H determination in Bi 2 Sr 2 Ca 1Ϫx Y x Cu 2 O 8ϩ␦ ͑Bi-2212͒ crystals with different doping levels. By combining cationic substitutions and oxygen pressure annealings, crystals with a doping state going from the underdoped to overdoped regime have been obtained. The corresponding ab (0) values, deduced from reversible magnetization measurements have allowed us to evidence a ''boomerang'' shape for the T c ͓1/ ab 2 (0)͔ curve in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
(40 reference statements)
4
16
0
Order By: Relevance
“…Similar results on Bi 2 Sr 2 Ca 1−x Gd x Cu 2 O 8+δ single crystals are reported by other authors [11].…”
Section: Second Peaksupporting
confidence: 80%
“…Similar results on Bi 2 Sr 2 Ca 1−x Gd x Cu 2 O 8+δ single crystals are reported by other authors [11].…”
Section: Second Peaksupporting
confidence: 80%
“…γ = 60 was obtained from angular resolved resistivity measurements using scaling arguments [27]. With κ 2 = λ ξ , B c2 = φ0 2πξ 2 , we find ξ (0) = 3.3nm, λ (0) = 2080nm consistent with the slightly overdoped regime [28]). The approximate field dependence of the critical current in a restricted field range is an indication but can not be taken as a proof of the validity of the model.…”
mentioning
confidence: 94%
“…It is known, that overdoping or underdoping of Bi 2 Sr 2 CaCu 2 O 8+δ can be achieved by cation substitutions or by changes in the oxygen content 41,42 . However, in the low-T c Bi-based phase Bi2201, we have found that it is difficult to change the number of holes, because it is difficult to change the oxygen content.…”
Section: Methodsmentioning
confidence: 99%